Writing retreats as third spaces - Garaway, J. (South African Journal of Higher Education, 2017)
Much has been written on the importance of writing retreats in providing the conditions for productive writing, away from the demands of everyday academic life. Most authors, however, acknowledge that even though retreats may result in positive outcomes, they are also complex social spaces which participants may experience as challenging. One, perhaps different, way to understand these difficulties is that they are the sorts of differences typical of a form of learning space known as a ‘third space’. In such spaces, as seen through an Activity Theory lens, differences can be understood as drivers for collaborative learning and development. Theorising writing retreats as third spaces within an Activity Theory framework then opens up ways to potentially enhance participants’ learning experiences.